IMPROVEMENT OF NON SPECIFIC IMMUNE SYSTEM ON COMMON CARP (Cyprinus carpio) AGAINST KOI HERPESVIRUS DISEASE (KHVD) BY ADDITION OF ASCORBIC ACID ON FISH DIET: A FIELD SCALE STUDY - Taukhid Taukhid; Desy Sugiani; Angela Mariana Lusiastuti (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
The research with the aim to know the optimal feeding frequency of supplemented ascorbic acid (microencapsulated vitamin C CFC-90) on the dose of 750 mg/kg feed to control Koi Herpesvirus (KHV) disease infecting common carp has been done in field condition. Fish were reared in floating cages with the size of 3.5 m x 3.5 m x 2.0 m and stocking density of 1,250 fish/cage with the size range of ± 10 g/fish. The treatments applied in the research were: (A) daily application, (B) every 3 days application, and (C) without vitamin C addition as the control. Fish test were challenged to KHV infection on the mid cultivation by cohabitation method in the laboratory scale for 2 weeks. Examination on behavior, clinical sign, and mortality of fish test conducted daily. The results showed that the highest survival rate was found on the application of vitamin C every 3 days (60.16%); and followed by every day (52.00%), and the lowest was found on the control group (47.36%).